2018
DOI: 10.1016/j.celrep.2018.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Projections of Layer Vb Neurons to Layers Va, III, and II in the Lateral and Medial Entorhinal Cortex of the Rat

Abstract: Layer V of the entorhinal cortex (EC) receives input from the hippocampus and originates main entorhinal outputs. The deep-sublayer Vb, immunopositive for the transcription factor Ctip2, is thought to be the main recipient of hippocampal projections, whereas the superficial-sublayer LVa, immunonegative for Ctip2, originates the main outputs of EC. This disrupts the proposed role of EC as mediating hippocampal-cortical interactions. With the use of specific (trans)synaptic tracing approaches, we report that, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
119
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(138 citation statements)
references
References 59 publications
18
119
1
Order By: Relevance
“…Moreover, we saw a gradient in this intrinsic excitability wherein cells located in ventral MEC require less current to fire an action potential compared to cells in dorsal MEC. The gradients in excitability that we report could provide a gating mechanism that prioritizes certain outputs from the MEC as deep MEC sends projections to various intrathalamic structures and LII of the MEC (Ohara et al, 2018;Sürmeli et al, 2015) whereas superficial MEC primarily projects to the hippocampus (Canto et al, 2008). This could also be relevant to the in vivo reports that grid cells with smaller spatial scales are present near the dorsal border while cells with a larger spatial scale are found more ventrally (Hafting et al 2005, Barry et al 2007, Brun et al 2008, Stensola et al 2012.…”
Section: Vip Cells Show Heterogeneity In Their Electrophysiological Asupporting
confidence: 57%
See 2 more Smart Citations
“…Moreover, we saw a gradient in this intrinsic excitability wherein cells located in ventral MEC require less current to fire an action potential compared to cells in dorsal MEC. The gradients in excitability that we report could provide a gating mechanism that prioritizes certain outputs from the MEC as deep MEC sends projections to various intrathalamic structures and LII of the MEC (Ohara et al, 2018;Sürmeli et al, 2015) whereas superficial MEC primarily projects to the hippocampus (Canto et al, 2008). This could also be relevant to the in vivo reports that grid cells with smaller spatial scales are present near the dorsal border while cells with a larger spatial scale are found more ventrally (Hafting et al 2005, Barry et al 2007, Brun et al 2008, Stensola et al 2012.…”
Section: Vip Cells Show Heterogeneity In Their Electrophysiological Asupporting
confidence: 57%
“…Our tracing experiments reveal that VIPs receive both local and long-range inputs thus providing for a dynamic routing of information to the MEC. Previous studies have shown that grid cells in LII of the MEC require hippocampal information to stabilize their firing fields (Bonnevie et al, 2013), and that this input is primarily received by cells in the deep layers , Ohara et al 2018. While cells from LVb project to the superficial layers (Ohara et al, 2018), our experiments revealed an additional route for this feedback to reach spatially tuned cells in layers II-III.…”
Section: Vip Cells Receive Input From Within the Mec The Mesencephalmentioning
confidence: 45%
See 1 more Smart Citation
“…Specifically, two layer 2 subtypes were classified as RELN + and one as CALB1 + (Witter et al, 2017). Other upper-layer subtypes were depicted based on marker gene expression of LAMA3 , PDGFD , IL1RAPL2 , and PCP4 (Ramsden et al, 2015; Tang et al, 2015; Ohara et al, 2018). The middle-to-deep layer subtypes were delineated by the specific gene expression of RORB , THEMIS , ADRA1A , and TLE4 .…”
Section: Methodsmentioning
confidence: 99%
“…Both Bcl11 genes are expressed during embryonic development as early as E10.5 and continuing to be expressed throughout life in several tissues like the brain, immune system, and skin (Leid et al, 2004;Golonzhka et al, 2007;Zhang et al, 2012). In the central nervous system, Bcl11 genes are expressed in the dorsal spinal cord, neocortex, hippocampus, entorhinal cortex, striatum, amygdala, and cerebellum ( Table 1; Leid et al, 2004;Arlotta et al, 2005Arlotta et al, , 2008Desplats et al, 2008;John et al, 2012;Simon et al, 2012;Canovas et al, 2015;Surmeli et al, 2015;Wiegreffe et al, 2015;Greig et al, 2016;Woodworth et al, 2016;Ohara et al, 2018). The best studied brain areas in relation to Bcl11 are the hippocampus, neocortex, spinal cord, and striatum.…”
Section: The Bcl11 Zinc-finger Transcription Factor Familymentioning
confidence: 99%